Metal complexes of tetradentate azo‐dye ligand derived from 4, 4′‐oxydianiline: Preparation, structural investigation, biological evaluation and MOE studies. (30th June 2020) - Deghadi, Reem G.; Mahmoud, Walaa H.; Mohamed, Gehad G.
Abstract : The Cr (III), Mn (II), Fe (III), Co (II), Ni (II), Cu (II) and Cd (II) complexes were prepared by reaction of its metal chlorides with new azo‐dye ligand (H2 L). The ligand derived from 4, 4′‐oxydianiline and 2‐amino‐4‐chlorophenol was synthesized in a 1:2 molar ratio. The structure of the ligand and its metal complexes was investigated using different tools such as elemental analysis (C, H, N and M), molar conductivity, IR, UV–vis, 1 H‐NMR, mass spectrometry and thermogravimetric and differential thermogravimetric studies. The data showed that the ligand acted as a N, N, O, O ‐binegative tetradentate ligand. All metal complexes had a octahedral structure as depicted by spectral and elemental analyses. The conductivity data showed the electrolytic nature of the Cr (III) and Fe (III) complexes while the other complexes were nonelectrolytes. Thermal analysis studies showed the decomposition of the complexes in four to five steps with the weight loss of hydrated water in the first decomposition step followed by the coordinated water and ligand molecules. Biological activity was tested for the prepared compounds against four bacterial species ( Bacillus subtilis, Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa ) and against two fungal species ( Aspergillus fumigatus and Candida albicans ). Also, all complexes were screened for anticancer activities against a breast cancer (MCF‐7) cell line. The [Co(L)(H2 O)2 ] complex showed the lowest IC50 value. Molecular docking is a key tool in computer drug design. Therefore, investigation of protein receptors and ligand interaction plays a vital role in the design of structurally based drugs. As a result, docking studies were investigated for H2 L ligand, [Mn(L)(H2 O)2 ] and [Ni(L)(H2 O)2 ] complexes with 5KBC, 3V7B and 4G9M receptors. Abstract : ‐ Azo dye ligand (H2 L) and its metal complexes were prepared and characterized using different techniques. ‐ Docking studies were investigated for H2 L ligand, [Mn(L)(H2 O)2 ] and [Ni(L)(H2 O)2 ] complexes with 5KBC, 3V7B and 4G9M receptors. ‐ The result of biological and anticancer activities of the ligand and its complexes was recorded.